TOXOPLASMA CHORIORETINITIS DIAGNOSED BY HISTOPATHOLOGY IN A PATIENT WITH AIDS. Issue Volume 9:Issues 2(2015:Spring) (2015) - Crosson, Jason N.; Laird, Philip W.; Grossniklaus, Hans E.; Hendrick, Andrew M.
Abstract : Purpose: To demonstrate the diagnostic difficulties in cases of retinal necrosis in immunocompromised patients including the potential for false-negative anterior segment sampling and also to emphasize the utility of diagnostic vitrectomy with histopathologic examination. Methods: This patient's chart was thoroughly reviewed to present salient features that are relevant to any ophthalmologist attempting to diagnose and treat chorioretinitis. A 38-year-old man with HIV/AIDS who presented with bilateral retinal necrosis. Thorough workup, including multiple samples of anterior chamber fluid for polymerase chain reaction, was negative. Results: Diagnostic vitrectomy revealed a toxoplasma cyst. Triple therapy stabilized retinitis, although vision did not improve. Conclusion: This case reminds the clinician to consider a broad differential diagnosis for retinal necrosis in immunocompromised hosts and, when serologic and anterior chamber samples are negative, to consider diagnostic vitrectomy for polymerase chain reaction and histopathologic examination. Abstract : This case demonstrates the atypical presentation of toxoplasmosis in immunocompromised patients, the diagnostic difficulties encountered, and the utility of diagnostic vitrectomy with histopathologic examination in such patients.